Pos Pemberdayaan PAUD Berbasis Masyarakat: Peningkatan Manajemen Pengelolaan PAUD (RA-TK-KB) Muslimat NU Kabupaten Wonosobo - Haryanto, Sri (Abdi Masyarakat, 2022)
Community service with the title Community-Based PAUD Empowerment Post: Improving Management of PAUD Management Muslimat NU Wonosobo Regency aims to improve the quality of management of Early Childhood education management organized by the community in this case is Muslimat NU Wonosobo Regency. The implementation of Early Childhood Education community participation is very important, so that efforts that can be made are to increase community participation in the implementation of Early Childhood Education, as an effort to increase awareness and active role of the community, be it social organizations (CSOs), social organizations (orsos) or local institutions that are deeply rooted in the community in the management of early childhood education (PAUD). This Tarbiyah Science-based Service Program is designed through planning, organizing, implementing, evaluating and reporting. From the stages of service that have been carried out for 6 months, an overview is obtained that in general: 1. Early Childhood Education Institutions managed by Muslimat have begun to organize themselves, especially in terms of institutional administration, 2. The idea came from the management of YPM Muslimat NU Wonosobo Regency to initiate the PAUD Posdaya model as an alternative in the success of community-based ECCE programs, 3. Management of the implementation of early childhood education organized and managed by Muslimat NU has been improved efforts, 4. The quality of management of early childhood education management muslimat NU Wonosobo district is getting better, 5. Public awareness of the importance of early childhood education is increasing, and 6. There is a positive cooperation between FITK UNSIQ and the ECCE Organizers.